Regulation of Hormone-Related Genes in Ericerus pela (Hemiptera: Coccidae) for Dimorphic Metamorphosis. Issue 5 (14th October 2019) - Pengfei, Liu; Weiwei, Wang; Xiaofei, Ling; Qin, Lu; Jinwen, Zhang; Rui, He; Hang, Chen
Abstract: Insect hormones regulate metamorphosis including that leading to sexual dimorphism. Using RNA-Seq, we discovered that the second-instar male larva (SM) of the white wax insect, Ericerus pela, have 5, 968 and 8, 620 differentially expressed transcripts compared with the second-instar female larva (SF) and the first-instar male larva (FM), respectively. The expression levels of genes involved in the apoptosis of old tissues and the reconstruction of new ones in the SM significantly enhanced, while the SF mainly has enhanced expression levels of anabolic genes such as chitin. We predicted that the second-instar larvae are the developmental origin of sexual dimorphic metamorphosis. Meanwhile, in the juvenile hormone (JH) metabolic pathway, CYP15A1 and JH esterase ( JHE ) are differentially expressed; and in the 20-hydroxyecdysone (20E) metabolic pathway, CYP307A1, CYP314A1, and CYP18A1 are differentially expressed. In the SM, the expression levels of CYP307A1 and CYP314A1 are significantly increased, whereas the expression level of CYP18A1 is significantly decreased; in the SF, the expression levels of the above genes are opposite to that of the SM. Expression trends of RNA-seq is consistent with the expression level of qRT–PCR, and seven of them are highly correlated ( R ≥ 0.610) and four are moderately correlated (0.588 ≥ R ≥ 0.542).